Adverse events during testosterone replacement therapy in 95 young hypogonadal thalassemic men - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Di Maio, Salvatore (Acta Biomedica Atenei Parmensis, 2019)
Background: Hormonal treatment of hypogonadism in thalassaemia major (TM) is a complex issue due to the co-existence of other contributing factors such as severity of iron overload, associated chronic liver disease and other endocrine complications. Objectives: Data about adverse events (AEs) of testosterone replacement therapy (TRT) in hypogonadal males with TM is scarce.We report the adverse events registered during TRT in 95 young patients with TM. Results: These AEs included gynecomastia, documented in 41/95 (43.1%) TM patients of mild to moderate severity (90%). Persistent pain in the injection site and local reactions to testosterone (T) skin patch occurred in a third of patients. Priapism was reported in 2 patients on treatment with intramuscular T enanthate. In both patients, substitution with T gel was successful, and no recurrence during the following 24 months was observed. Conclusions: Clinicians should exercise caution when considering TRT for hypogonadal men with TM. (www.actabiomedica.it)